Extending the gamma concept to non-thermal inactivation: A dynamic model to predict the fate of Salmonella during the dried sausages process. (February 2015) - Coroller, Louis; Jeuge, Sabine; Couvert, Olivier; Christieans, Souad; Ellouze, Mariem
Abstract: The process of dried fermented sausages is recognized to be favourable to the reduction of the Salmonella population. The objective of this study was to develop a model describing the evolution of Salmonella during the fabrication process of dried sausages and to optimize the food formulation to prevent pathogen presence at the end of the process. An experimental design was set to investigate the effects of the fermentation and drying process for several formulations, taking into account the type of starter culture, the sodium chloride concentration, the dextrose and lactose concentration on the Salmonella Typhimurium strain behaviour. A growth-inactivation model based on the gamma concept was then developed to quantify Salmonella behaviour in dynamic process conditions of temperature, pH, lactic acid and water activity. This behaviour was characterized by a first growth step, followed by an inactivation step. The Salmonella fate was well described by the model in terms of population size variation and transition from growth to inactivation. The Salmonella behaviour was influenced by the initial sugar concentration and the starter type but not by sodium chloride content. This model can be a valuable tool to design the food process and formulation to control Salmonella . Highlights: Bacterial growth and inactivation in dynamic environmental conditions were modelled. Drying is an essential step to control the safety of fermented sausage. a w and lactic acid are essential to inhibit growth and to ensure inactivation.